The Interpretation of Tsamanan Qalīlan in the Qur'an (A Thematic Study) - Rambe, Irpan; Dwi Rahma Zura; Meli Eliza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the author's interest in the frequent use of the phrase Tsamanan Qalīlan in the Qur'an. The phrase Tsamanan Qalīlan appears at least 10 times in the Qur'an, although there are 9 verses with similar meanings. Furthermore, the phrase occurs in different surahs. Tsamanan Qalīlan means